The Causes of Conflicts in the Contracting Processes on the Internet - Murad Saib Mahmood, Zana Ismael Aziz, Hallo Mohammed Salih Abdulsamad, (Opción, 2019)
The aim of this paper is to examine the causes of conflicts in thecontracting processes on the Internet. The methodology used in thispaper is pure library research focusing mainly on primary andsecondary sources. As a result, the application of the principle ofchildhood and even some other types of contracts on the Internet hasbeen considered as another problematic case of contracting on thewebsites. In conclusion, consumer protection in international contractshas become necessary, and that protection requires the development ofconsumer protection provisions, especially with regard to the terms andconditions of Internet sites.